The transcription factor PoMbp1 promotes the growth and development of Pleurotus ostreatus by regulating polysaccharide utilisation - Lijiao Zhang; Yingjie Zhang; Zeyin Wu; Mengran Zhao; Xiangli Wu; Chenyang Huang (Mycology)
The transcription factor Mbp1 was reported to regulate cell growth and proliferation in some fungi; however, its role in Pleurotus ostreatus remains largely unexplored. Here, we cloned the PoMbp1 gene, which encodes a protein contains an APSES domain and is localised in the nucleus. The expression pattern analysis showed that PoMbp1 was expressed more in the caps of the fruiting body than in other stages. The growth rates of the PoMbp1 overexpression strains OE-PoMbp1 were similar to those of wild-type, while that in the interference strains RNAi-PoMbp1 were markedly reduced, indicating that PoMbp1 positively regulates P. ostreatus development. Transcriptome sequencing showed that the DEGs between PoMbp1 transformants and wild-type mainly enriched in carbohydrate metabolism, cell growth and death, etc. The DEGs in polysaccharide catabolic were highly expressed in the OE-PoMbp1 strains. Treat PoMbp1 transformants with different monosaccharides and polysaccharides, the OE-PoMbp1 strains grew faster than wild-type on medium containing polysaccharide, whereas no differences were observed with monosaccharides. The RNAi-PoMbp1 strains showed an opposite trend. These results indicated that PoMbp1 plays a positive role in fruit body development by enhancing the expression of genes related to polysaccharide utilisation. This study provides a theoretical reference for research on the mechanism of fruiting body development of P. ostreatus.